Otherness' in Space and Architecture Jews, Muslims and Christians in Western European Art (1200-1650) - Portmann, Maria (Peter Lang International Academic Publishing Group, 2021)
This conference proceeding (Sessions on "Otherness in Space and Architecture", International Medieval Conference, Leeds, 2017 and 2018) is a compilation of articles written by both young and senior scholars, who are working on the question of the 'self' and the 'other' in Christian, Jewish and Islamic cultures. The articles examine how material, 'oriental' objects and knowledge originating in non-Western communities helped building and strengthening the identity of Iberia's, southern France and northern Italian nobility and its lineages. It is shown how, in the perception of Christians, the public image of Jews and Moslems became constructed as that of adversaries, while their cultural knowledge, at the same time, would be integrated into Christian culture in a paradox manner, in which the 'self' necessarily depends on the 'other' and how visual tensions in art and space have been used as symbols of power.